Proposal for a modification of the UVI risk scale - Zaratti, Francesco (2014)
The standardisation of UV information to the public through the UV Index (UVI) has been hugely beneficial since its endorsement by multiple international agencies more than 10 years ago. It has now gained widespread acceptance, and UVI values are available throughout the world from satellite instruments, ground-based measurements, and from forecasts based on model calculations. These have been useful for atmospheric scientists, health professionals (skin and eye specialists), and the general public. But the descriptors and health messages associated with the UVI scale are targeted towards European skin types and UV regimes, and are not directly applicable to the population living closer to the equator, especially for those in the high-altitude Altiplano region of South America. This document arose from discussions at the Latin American Society of Photobiology and Photomedicine´s Congress, which was held in Arequipa, Peru, in November 2013. A major outcome of the meeting was the Arequipa Accord, which is intended as a unifying document to ensure co-ordination of UV and health research decisions in Latin America. A plank of that agreement was the need to tailor the UVI scale to make it more relevant to the region and its population. Here we make some suggestions to improve the international applicability of the UVI scale.